Write it when I'm gone : remarkable off-the-record conversations with Gerald R. Ford - DeFrank, Thomas M.; Ford, Gerald R., 1913-2006. (New York : G.P. Putnam's Sons, 2007)
In an series of private interviews, conducted over sixteen years with the stipulation that they not be released until after his death, the 38th President of the United States reveals a profoundly different side of himself: funny, reflective, gossipy, strikingly candid. In 1974, journalist DeFrank, then a young correspondent for Newsweek, was interviewing Vice President Gerald R. Ford when Ford blurted out something indiscreet, came around his desk, grabbed DeFrank's tie, and told the reporter he could not leave the room until he promised not to publish it. "Write it when I'm dead," he said--and that agreement formed the basis for their relationship for the next 32 years. During that time, they talked frequently, but from 1991 to shortly before Ford's death, the interviews became unguarded conversations in which Ford talked in a way few presidents ever have.--From publisher description.
Includes index.
Keywords: Ford, Gerald R., -- 1913-2006.; Ford, Gerald R., -- 1913-2006 -- Interviews; Presidents -- United States -- Biography; Presidents -- United States -- Interviews; United States -- Politics and government -- 1974-1977.; United States -- Politics and government -- 1977-1981.; United States -- Politics and government -- 1981-1989.; United States -- Politics and government -- 1989-; DeFrank, Thomas M